Student Language Anxiety in Learning English (A survey to non-English Major students in rural area) - Tuti Hidayati (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2018)
Learners’ difficulties in learning a foreign language cannot merely be linked to the lack of ability or intelligence. Language anxiety or the feeling of tension, apprehension, fearfulness, and worry in language class had been pointed to greatly influence learner’s progress in mastering the target language. Highly anxious learners were found to achieve less and had low motivation. This study reports a survey investigating the level of language anxiety and its perceived causes and discusses some alternatives to deal with it. The participants were 114 non-English major students in State Islamic College of Teungku Dirundeng Meulaboh in West Aceh. Data were collected employing Foreign Language Classroom Anxiety Scale developed by Horwitz, Horwitz, and Cope, (1986). The finding indicated that the students participating in the study exhibited a moderate level of language anxiety obtaining FLCAS mean score 102.17. The main cause of language anxiety was attributed to fear of negative evaluation with the highest average mean 3,5. Communication apprehension and test anxiety were in the second and third rank with the average mean 3,3 and 3,1 respectively. Meanwhile, English classroom items were perceived to contribute the least to the students’ tense experience given the average mean 2,7. It is suggested that making the learners realize that they are not alone experiencing anxiety in learning a foreign language is crucial. Furthermore, it is important that teachers embrace a supportive and non-threatening role to provide a more effective foreign language learning.